Unfolding the Lived Experiences of the College Students’ Language Learning Strategies vis-à-vis their English Proficiency: A Convergent Design - RAYMUNDE, PEDRO JR; Mamonong, Virgion H. (International Journal of Language and Literary Studies, 2022)
The study determined students’ language learning strategies (LLS) status and English proficiency (EP). A mixed-method, particularly the convergent design, was used. Through purposive sampling, 378 and 17 Education major in English students served as participants for the quantitative and qualitative strands. An adapted questionnaire for quantitative strand and interview guide for qualitative strand were used to gather the necessary data. The study revealed a high level of LLS and a low level of EP. The compensation strategy has a significant relationship to EP. Six themes unfolded as the lived experiences in learning English: sustaining interest amidst fear, looking through an uphill battle, experiences enrich communicative competence, courage to face adversities, igniting positive language learning, and translating excellence in multilingual contexts. Regarding the insights on the contribution of English LLS, five themes emerged: a window of opportunities, towering the students' lamp, guarding with a bulletproof vest, dreaded fires of mediocrity, and kindling brighter lamps through assistance. Moreover, the joint display of quantitative and qualitative findings yielded that students' LLS and their lived experiences are convergent when the merging function is employed; EP status and experiences are convergent when the merging function is employed. However, on the relationship of LLS on the EP of the students, the results show the merging functions as diverging. Further, only the compensation strategies have a significant relationship with the EP of the students.